The relationship between body mass index and frog jumping ability in elementary school students - Naharini, Fadilatul Arofa; Nurrochmah, Siti; Dewi, Dyas Sasmita; Ramadhan, Muhammad Nova (Multilateral : Jurnal Pendidikan Jasmani dan Olahraga, 2025)
The development of fundamental movement skills during childhood plays a crucial role in enhancing physical activity and maintaining overall health throughout life. This study aims to analyze the relationship between Body Mass Index (BMI) and children's motor skills, particularly in the frog jump test. The study employs a correlational approach with a sample of 120 upper-grade elementary school students (grades 4, 5, and 6) from SDN Gadingkasri and SDN Oro-Oro Dowo in Malang City. The subjects consist of 63 students from SDN Gadingkasri and 57 students from SDN Oro-Oro Dowo, with a balanced gender composition and an age range of 9–12 years. Measurements include body weight and height. The results indicate a significant relationship between anthropometric measurements and children's frog jumping ability. Children with a normal BMI demonstrate better motor skills compared to those who are underweight, overweight, or obese. The implications of this study highlight the importance of regular nutritional status monitoring and the development of children's motor skills through appropriate nutritional interventions and structured physical exercise programs in schools. Collaboration between schools, parents, and communities is essential to ensure optimal motor development in elementary school-aged children.